Multiple losses and transfers to the nucleus of two mitochondrial succinate dehydrogenase genes during angiosperm evolution. - Adams, K L (2001)
Unlike in animals, the functional transfer of mitochondrial genes to the nucleus is an ongoing process in plants. All but one of the previously reported transfers in angiosperms involve ribosomal protein genes. Here we report frequent transfer of two respiratory genes, sdh3 and sdh4 (encoding subunits 3 and 4 of succinate dehydrogenase), and we also show that these genes are present and expressed in the mitochondria of diverse angiosperms. Southern hybridization surveys reveal that sdh3 and sdh4 have been lost from the mitochondrion about 40 and 19 times, respectively, among the 280 angiosperm genera examined. Transferred, functional copies of sdh3 and sdh4 were characterized from the nucleus in four and three angiosperm families, respectively. The mitochondrial targeting presequences of two sdh3 genes are derived from preexisting genes for anciently transferred mitochondrial proteins. On the basis of the unique presequences of the nuclear genes and the recent mitochondrial gene losses, we infer that each of the seven nuclear sdh3 and sdh4 genes was derived from a separate transfer to the nucleus. These results strengthen the hypothesis that angiosperms are experiencing a recent evolutionary surge of mitochondrial gene transfer to the nucleus and reveal that this surge includes certain respiratory genes in addition to ribosomal protein genes.